2004
DOI: 10.1148/radiol.2323030573
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Myocardial Perfusion in Canines Measured by Using Dual-Bolus First-Pass MR Imaging

Abstract: Dual-bolus MR imaging enabled accurate measurement of absolute epicardial and endocardial perfusion across a wide range of blood flow rates (0 to >5.0 mL/min/g). Use of qualitative MR imaging measures such as the contrast enhancement ratio led to substantially underestimated hyperemic blood flow measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
259
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(267 citation statements)
references
References 22 publications
8
259
0
Order By: Relevance
“…The dual-sequence method (1,4) obtains these measurements in the same cardiac cycle, while the dual-bolus method (2,3) uses separate low-and high-dose first passes for the AIF and myocardial measurements, respectively. The dual-bolus and dual-sequence methods agreed reasonably well in previous in vivo studies (1), and the dual-bolus method has been validated against microspheres as the gold standard (2).…”
supporting
confidence: 56%
“…The dual-sequence method (1,4) obtains these measurements in the same cardiac cycle, while the dual-bolus method (2,3) uses separate low-and high-dose first passes for the AIF and myocardial measurements, respectively. The dual-bolus and dual-sequence methods agreed reasonably well in previous in vivo studies (1), and the dual-bolus method has been validated against microspheres as the gold standard (2).…”
supporting
confidence: 56%
“…PBF and PBV values were calculated for all single-bolus measurements, which means that AIF and tissue signal-time courses were taken from the same datasets for contrast agent doses of 0.5 mL, 1.0 mL, 2.0 mL, and 3.0 mL, respectively. Additionally, PBF and PBV were calculated using the prebolus approach (14,15). The prebolus technique consists of a combination of two measurements.…”
Section: Theorymentioning
confidence: 99%
“…With the application of higher doses, signal saturation occurs, which leads to underestimation of the actual concentration. This problem was investigated by different groups working on contrast-enhanced perfusion quantification with MRI of different tissues, and several techniques have been proposed to overcome this limitation (11)(12)(13)(14)(15). One promising technique is the prebolus (or dual-bolus) approach, which was initially proposed for quantification of myocardial perfusion (14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The large-contrast bolus that is used to determine the myocardial response provides adequate signal to noise ratio. The implementation of the prebolus has shown to provide absolute perfusion values comparable to perfusion values determined by microspheres in animals (5,6) and positron emission tomography (PET) in healthy volunteers (7). Kurita et al (11) showed that regional myocardial perfusion reserve (MPR) determined by using dual-bolus MR-MPI correlated well to coronary flow reserve by intracoronary Doppler flow wire in patients with suspected coronary artery disease (CAD).…”
mentioning
confidence: 99%